Hazard Identification and Job Safety Analysis for Improving Occupational Health and Safety in Fishing Net Sinking Process in Southern Thailand - Mahaboon, Junjira; Yimthiang, Supabhorn; Waeyeng, Donrawee; Darnkachatarn, Siriporn (International Journal of Integrated Engineering, 2022)
The fishing net sinker workers are exposed to numerous workplace hazards that can endanger their health and safety.  We utilized a walk-through survey and Job Safety Analysis (JSA) technique to assess each step of the work process, identify potential hazards on each job and suggest the safest approach to fishing net sinker workers in southern Thailand. A JSA is a useful tool for mitigating risk in the workplace. It emphasizes the interaction between workers, tools or equipment, the working environment, and the tasks. The results show that a total of 52 potential hazards occur with varying severity and likelihood, 20% of which are categorized at the highest level. The mesh and lead ball making activities carry an extreme risk rating (RR=12). This work has possible hazards, namely occupational lung and asthma disorders. 40% are categorized at the high-risk level, namely fingers cut by tools (RR=8), and repetitive strain disorder (RR=8). Workers can be more proactive in implementing health and safety measures through appropriate risk control. The result of the paired-sampleâ€™s t-test showed that the average risk score differs before taking control measures (M= 7.54, SD = 2.62) and after taking control measure (M= 4.31, SD = 1.55) at the 0.0001 level of significance (t = 7.6513, df = 51, n=52, P< 0.0001, 95% confidence interval of this difference 2.39 to 4.07). On an average, risk reduction was about 3.23 point lower after taking control measures. Ensuring that workers use tools and equipment safely and also that they maintain this equipment properly. Thus, it was suggested that the government agencies concerned should carry out regular surveillance and further develop the learning process and solutions to work safety procedures as guidelines to improve their safety, wellbeing, and working conditions. These enhancements will also contribute to the higher efficiency and effectiveness of their work and advance the dynamic interest and participation of the fishing net sinker workers in other areas, including careers for the informal workers of similar work characteristics.Keywords: hazard identification, job safety analysis, occupational health and safety, walk-through survey, fishing net sinker